Personal Hygiene dalam Pencegahan Infeksi Soil Transmitted Helminth - Nayla Priyanka Dara Tsanya; Terza Aflika Happy; Betta Kurniawan; Jhons Fatriyadi Suwandi (Medula, 2026)
Soil-transmitted helminth (STH) infection is a disease caused by intestinal nematode worms transmitted through contaminated soil. The STH species that most commonly infect humans include Ascaris lumbricoides, Trichuris trichiura, Ancylostoma duodenale, and Necator americanus. STH infection remains a global public health problem and is estimated to affect more than 1.5 billion people worldwide, particularly in developing countries with tropical and subtropical climates and inadequate sanitation conditions. Among school-aged children, STH infection is one of the most frequently encountered forms of helminthiasis due to suboptimal hygiene-related behaviors. This infection can lead to various adverse health outcomes, including impaired nutrient absorption, poor nutritional status, reduced learning ability, and delays in children’s growth and development. This literature review aims to provide an overview of the role of personal hygiene, including handwashing with soap, nail hygiene, and the use of footwear, in preventing STH infection among  children. The findings indicate that the prevalence of STH infection among children with poor personal hygiene ranges from 24% to more than 80% in several endemic areas. Children who do not wash their hands with soap are reported to have a 6–9 times higher risk of infection compared to those who practice good hygiene. Poor nail hygiene and not wearing footwear are also associated with an increased risk of infection. This literature review emphasizes that personal hygiene plays a crucial role in preventing STH infection and reinfection among children and should be strengthened as part of school-based promotive and preventive strategies.